1937
DOI: 10.1098/rspb.1936.0076
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of action of pituitary hormones by animal sera

Abstract: The experiments were aided by a grant from the Josiah Macy, jr., Foundation. * Mentioned because of the possible relationship to the formation of immune bodies This applies also to extract No. 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1937
1937
1969
1969

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Thompson and Cushing (1937) found that the antiserum to extract of pregnant mare serum, prepared in a dog, would only partially inhibit the gonadotropic activity of an extract of sheep or pig pituitary, or of human urine of pregnancy. The serum of two dogs immunized with extract of sheep pituitary was less specific, and neutralized extracts of pig pituitary, human urine of pregnancy, human urine of menopause and pregnant mare serum.…”
mentioning
confidence: 99%
“…Thompson and Cushing (1937) found that the antiserum to extract of pregnant mare serum, prepared in a dog, would only partially inhibit the gonadotropic activity of an extract of sheep or pig pituitary, or of human urine of pregnancy. The serum of two dogs immunized with extract of sheep pituitary was less specific, and neutralized extracts of pig pituitary, human urine of pregnancy, human urine of menopause and pregnant mare serum.…”
mentioning
confidence: 99%